Metaverse-Based Islamic Religious Education: Reimagining Immersive Learning for Future Islamic Classrooms - Markhabat Bolat; Mohammad Ahmad Bani Amer; Khalid Abdullah Al Muzaini; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
The development of the metaverse introduces new possibilities for immersive, interactive, and collaborative educational experiences. However, scholarly discussions regarding its application in Islamic Religious Education remain scarce. This study aims to explore the pedagogical potential of metaverse technology in creating meaningful Islamic learning experiences while preserving religious values. A design-based research methodology was implemented through prototype development, expert validation, pilot implementation, and user evaluation involving teachers and university students. Data were collected through usability testing, interviews, learning achievement assessments, and user experience surveys. The findings indicate that metaverse-based learning enhances student engagement, collaborative interaction, experiential understanding of Islamic history, and practical learning of religious rituals through virtual simulation. Nevertheless, issues related to accessibility, digital ethics, infrastructure readiness, and religious authenticity require careful consideration. The novelty of this study lies in introducing the Islamic Metaverse Learning Ecosystem, an instructional framework integrating immersive technology, Islamic pedagogy, collaborative learning, and ethical digital engagement for future Islamic education.